PENINGKATAN HASIL BELAJAR MELALUI PENDEKATAN CULTURALLY RESPONSIVE TEACHING DI KELAS IV SD - Windi Sundari; Bekti Wirawati; Nunuk Suliyastuti (Al-SAMBASY: Jurnal Kajian Pendidikan, 2025)
This study is an action research aimed at improving the learning outcomes of in the Social and Natural Sciences (IPAS) subject on the topic of the Greenhouse Effect among Grade IV D students at SDN Pakis 01 Surabaya, consisting of 28 students. The data collection methods used included observation, tests, and documentation. The approach applied was the Culturally Responsive Teaching (CRT) approach. The research results showed that the implementation of the Culturally Responsive Teaching (CRT) approach significantly improved students' learning outcomes in the IPAS subject on the greenhouse effect topic. The pre-cycle results showed a mastery level of 46.43%, which increased to 60.71% in Cycle I, and further rose to 89.28% in Cycle II. The implementation of the Culturally Responsive Teaching approach successfully achieved the targeted outcomes and effectively improved IPAS learning results for Grade IV D students at SDN Pakis 01 Surabaya in the 2024/2025 academic year. The Culturally Responsive Teaching approach integrates students' values, habits, and cultural backgrounds into the learning process, making learning more relevant, meaningful, and empowering for students.